أثر تكنولوجيا المعلومات في أداء العاملين في مصرف التسليف الشعبي دراسة تطبيقية في فرع جبلة لمصرف التسليف الشعبي (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يعدّ مصرف التسليف الشعبي من المصارف الحكومية العريقة, وكغيره من المؤسسات المالية سعت إدارته لبلورة أعماله تقنيا, وتطوير أداء العاملين فيه, وتحسين مستوى الخدمات المقدمة من (ودائع, حسابات جارية, شهادات استثمار, قروض ). وبناء على ذلك تناول البحث بالترتيب أهم الأفكار التي تخدم موضوع البحث وفقاً لمايلي : 1-  أهم التقنيات المستخدمة في العمل المصرفي . 2-  أداء العاملين في مصرف التسليف . 3-  أثر التقنيات المستخدمة في تحسين أداء العاملين في مصرف التسليف الشعبي . وقد قمنا بتطبيق الدراسة على فرع جبلة لمصرف التسليف وتبين لنا أن التقنيات الموجودة فيه غير كافية لتطوير الأداء , ولا تلبي ضغط العمل المصرفي الذي يتميز به هذا الفرع  بأقسامه كافةً.  Pubular Cridet Bank is considered the most efficient bank among others. The Adminstration of the Pubular Cridet Bank worked to external the banking works through technology and develope employees performance and improve the services of ( Deposits , Current account , loans ,…etc).      This Study handles the important concepts in the list below : 1- The most important technology used in the bank. 2- Employees performance in the bank. 3-The effect of the technology in improving employees performance in the Pubular Cridet Bank. This stydy has been implemented at Jablah branch and the result showed that the available technology is not enough to develop the work performance and not enough to accommodate the pressur of banking work in all the department of the bank.